A Design of Smart Biometric Fingerprint Key Storage Cabinet Based on IoT - Thanat Nonthaputha; Montree Kumngern; Sompong Kaewwang; Jirapat Phookwantong; Nawaphol Thepnarin; Kravee Anontree (My University, 2022)
A design of smart biometric fingerprint key storage cabinet based on internet of things (IoT) is presented as a case study of machine – basic technical workshop at Rajamangala University of Technology Srivijaya (RUTS). A key storage cabinet in the box has been designed by circular slot to keep 20 keys and the maximum is for 20 machineries. The students can take a key by themselves by using a fingerprint scanning to register the database. Moreover, name, surname, levels of user, time and machinery number, etc can be saved to a database and it has to access by using password with administrator logging-in only. The proposed scheme can find a missed key machinery number and it has two speakers for a guiding voice. All keys are conveniently borrowed and returned by students. The administrator’s mobile phone will be received several data from the database via messages in Line application.
Keywords: IoT Networks and Protocols; IoT-based Smart Home Systems; RFID technology advancements